P-E3 HCV Treatment Lost to Follow-up: Comparing HIV/HCV infected and HCV infected Patients. (March 2017) - Silk, Rachel; Gross, Chloe; Akoth, Elizabeth; Ahmed, Charisee; Thomas, Aurielle; Masur, Henry; Kattakuzhy, Sarah; Kottilil, Shyam
Abstract : Background: Direct-acting antivirals have high rates of SVR, however, there remain significant challenges to completing treatment. HIV/HCV infected patients are already linked to care and presumably are less likely to be lost to follow-up during HCV treatment. Methods: Data from 2 groups in the observational study ASCEND were analyzed; those lost to follow-up post consent but prior to starting LDV/SOF (n = 81) and those lost during treatment (n = 57), in order to determine the effect of HIV/HCV infection on lost to follow up rates. Results: Eighty-one patients were lost to follow-up post consent; 15 HIV/HCV infected and 66 HCV infected. Over 50% of both cohorts were unreachable despite multiple attempts (53% (n = 8) HIV/HCV infected and 55% (n = 36) HCV infected). Of the 600 who were started on LDV/SOF between May and November 2015, 143 were HIV/HCV infected (1 tri-infected) and 457 were HCV infected (2 HCV/HBV). Fifty-seven patients were lost to follow-up while on treatment; 15 (10%) HIV/HCV infected and 42 (9.2%) HCV infected ( P = 0.62). There was also no difference in adherence to visits for week 4, 8 and 12 during treatment between the 2 cohorts. Conclusions: Our results show that HIV/HCV infected patients are just as likely as HCV infected patients to be lost to follow-up during treatment. Engaging all patients in care through SVR12 requires vigorous outreach regardless of current linkage to care. Strategies focused on retention in care should remain a priority.